Elaboração e caracterização de concentrado proteico deslipidificado à partir do uso de resíduos da filetagem de tambatinga (Colossoma macropomum X Piaractus brachypomum) - Cassol, Geodriane Zatta (2020)
Currently, 70% of processed fish is considered waste, but it could be used for human consumption, it still has marked nutritional value. Among the by-products that can be prepared, the Fish Protein Concentrate (FPC) stands out for its high protein content. However, to increase the versatility of this product and to avoid possible sensory interference caused by the concentration of lipids, in some cases, it is interesting to carry out a delipidification step, with different methods and solvents being used. Given this premise, the objective of this work was to compile information, already existing in the literature, about the different types of FPC, methods of obtaining, types of solvents that can be used in their delipidification and products that can be prepared with this raw material. In addition, an experimental test for the preparation of FPC from the residues of the filleting of tambatingas was also carried out, using organic solvents (hexane and ethanol) and the Soxhlet and Bath-equipment, in order to identify the efficacy of delipidification and characterization nutritional constituents of the final product. According to the literature consulted, there are three different types of FPC, which vary according to protein and lipid content (A, B and C). In addition, physical and chemical methods are the most used in the preparation of this product and hexane and ethanol are the most frequently used solvents. Due to its excellent nutritional value, it can be used to enrich food products. In the experimental test, tambatinga fillet residues (Colossoma macropomum X Piaractus brachypomum), from the fish processing industry, located in Mato Grosso, were used. The residues were crushed, homogenized (T0) and dried in an oven for 15 hours at 65ºC (T1) and then subjected to delipidification processes, where: T2 = delipidification by Soxhlet, using ethanol; T3 = delipidification by Soxhlet, using hexane; T4 = delipidification by water bath, using ethanol and T5 = delipidification by water bath, using hexane. Analyzes of nutritional composition and caloric value were performed for all treatments, in addition to yield, water activity, colorimetry, mineral composition and bioaccessibility of crude protein for all treatments, except T0 because it is raw material. The profile and bioaccessibility of amino acids for T3 and T5 were also determined, in addition to sensory analysis for T3, as these are the treatments with the greatest nutritional potential and lipid extraction. Good yields were observed in the FPC elaboration processes (33.08, 71.67%), low water activity (0.20), excellent protein content (58-85%), amino acids (lysine (2.08 g) .100-1)) and mineral (calcium (10255 - 13235 mg.100g-1) and phosphorus (12153 - 14054 mg.100g-1)). In addition, it has excellent protein bioaccessibility (T1 = 54%, T2 = 51%, T3 = 74%, T4 = 50% and T5 = 70%) amino acid and sensory acceptance for the attributes color (78%), texture (72%) and global impression (72%). FPCs showed high values of luminosity (L) (74.67), and low values of red / green scale (a *) (3.15) and yellow / blue scale (b *) (19.07). It is concluded that the FPC has technological and nutritional potential to be used as an ingredient in the preparation and enrichment of foods and that the Soxhlet method using n-hexane, used for delipidification, was not efficient for deodorizing the FPC, since the judges detected the presence of rancid and fishy odor, however it was efficient in lipid extraction.